The Impact of Physiopathy Natures on Acceptance of Fraud Behavior on Accounting with Financial Security as a Moderating Variable - Nursida Dewi; Hamidah Hamidah (Budapest International Research and Critics University, 2022)
Previous studies have supported the notion that Economics and Business students are more likely to have higher scores for psychopathic traits, but research has not been conducted to support whether this inherited trait has direct implications for the future likelihood that these students will take on an important role in the survival of the company, or whether their choice to study economics and business at the undergraduate and graduate levels has something to do with their inherited psychopathic traits. The question that this study aims to answer is whether the influence of psychopathic traits on acceptance of fraud is relatively higher when their financial resilience is better. A quantitative approach with SEM AMOS 22 and SPSS 22 was used to conduct the research. Respondents are active accounting graduate students in various universities with minimum accreditation B. The results of this study support both hypotheses, the first hypothesis is that psychopathic traits will affect acceptance of accounting fraud, and the second hypothesis is that the interaction between financial resilience and psychopathic traits affects the relationship between psychopathy and acceptance of accounting fraud.